EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK PEMBERIAN INFORMASI UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA - Sekar Kamiliya Salsabila; Nelly Fitriani; Dona Fitri Annisa (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to increase self-confidence and determine the effectiveness of group guidance services with information-giving techniques in increasing the self-confidence of class VIII students at SMPN 39 Bandung.This study uses a mix method research method, which combines quantitative and qualitative methods using the Explanatory Sequential Design design. The research sample of 10 students through purposive sampling technique based on certain considerations was taken with a sample category of having low and medium self-confidence. The data analysis technique used in this study used validity test, reliability test, normality test, homogeny test, paired t-test and N-gain test with the help of SPSS version 22. The results of the study showed a significant influence in increasing students' self-confidence as seen from the results of the T-Test, namely obtaining a t-count value of -10.003 with a significance level (2-tailed) <significance level of 0.000 <0.05 which means H0 is rejected and H1 is accepted. After being given group guidance services with information-giving techniques, students experienced an increase in self-confidence.